Perception of Saudi undergraduate medical students on telemedicine training and its implementation - Dalia Y M. El Kheir; Nour S AlMasmoom; Mariam K Eskander; Reem A Alshamrani; Rawaa N Alwohaibi; Fatimah N AlTheeb; Bedour A Aleid (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: The use of telemedicine has increased considerably in healthcare delivery, especially during this time of the coronavirus disease 2019 (COVID-19) pandemic. It has, therefore, become necessary to train medical students to better equip them for this new means of healthcare delivery. The aim of the present study was to assess the perception of undergraduate medical students on telemedicine training. MATERIALS AND METHODS: A cross-sectional study was conducted on a total of 521 undergraduate medical students studying in the Eastern Region of Saudi Arabia. Data were collected via a self-administered pretested questionnaire comprising two main sections: demographics and knowledge and opinions regarding telemedicine training. RESULTS: About 73% students think that the use of telemedicine for patient care will increase in the future, and 59.3% think that the medical students should be trained in telemedicine. Majority of the students (78%) opined that telemedicine training should be optional and 58% said it should be taught during the clinical phase of the undergraduate curriculum. The best telemedicine training course learning objectives medical students opined to be included were: telemedicine practical skills (70.2%), legal aspects of telemedicine practice (68.3%), and potential positive and/or negative use of telemedicine tools and methods (67.6%). Telemedicine skills students would like to learn how to effectively engage patients, knowledge about telemedicine regulations and the consequences of breaching them. CONCLUSION: Medical students are aware of the importance of incorporating telemedicine training into the medical curriculum. Training these students is vital to ensure their competence as physicians in their future clinical careers, that is make them a digitally health-literate future workforce.